Identification and Epidemiology of Severe Respiratory Disease due to Novel Swine-Origin Influenza A (H1N1) Virus Infection in Alberta. Issue 4 (2010) - Zahariadis, George; Joffe, Ari R; Talbot, James; deVilliers, Albert; Campbell, Patricia; Pabbaraju, Kanti; Wong, Sallene; Bastien, Nathalie; Li, Yan; Mitchell, Robyn L; Pang, Xiao-Li; Yanow, Stephanie; et al.
Abstract : BACKGROUND: In March 2009, global surveillance started detecting cases of influenza-like illness in Mexico. By mid-April 2009, two pediatric patients were identified in the United States who were confirmed to be infected by a novel influenza A (H1N1) strain. The present article describes the first identified severe respiratory infection and the first death associated with pandemic H1N1 (pH1N1) in Canada. METHODS: Enhanced public health and laboratory surveillance for pH1N1 was implemented throughout Alberta on April 24, 2009. Respiratory specimens from all patients with a respiratory illness and travel history or those presenting with a severe respiratory infection requiring hospitalization underwent screening for respiratory viruses using molecular methods. For the first severe case identified and the first death due to pH1N1, histocompatibility leukocyte antigens were compared by molecular methods. RESULTS: The first death (a 39-year-old woman) occurred on April 28, 2009, and on May 1, 2009, a 10-year-old child presented with severe respiratory distress due to pH1N1. Both patients had no travel or contact with anyone who had travelled to Mexico; the cases were not linked. Histocompatibility antigen comparison of both patients did not identify any notable similarity. pH1N1 strains identified in Alberta did not differ from the Mexican strain. CONCLUSION: Rapid transmission of pH1N1 continued to occur in Alberta following the first death and the first severe respiratory infection in Canada, which were identified without any apparent connection to Mexico or the United States. Contact tracing follow-up suggested that oseltamivir may have prevented ongoing transmission of pH1N1.